Emoji as Icebreakers? Emoji can signal distinct intentions in first time online interactions. (April 2022) - Rodrigues, David L.; Cavalheiro, Bernardo P.; Prada, Marília
Highlights: Emoji have been used to overcome potential limitations to written communication. Two experimental studies examined the role of emoji use in first time interactions in social networking platforms. When receiving messages, signaled friendship, and signaled romantic, and and signaled sexual intentions. When sending messages, signaled friendship, and signaled romantic, and signaled sexual intentions. Abstract: Very few studies have examined if emoji play a role in first-time interactions and whether their use conveys information about relationship initiation intentions. In two experimental studies ( N = 758), we explored if using different emoji to initiate interactions with strangers on Facebook and Tinder were perceived to signal distinct intentions from the sender (Studies 1 and 2) and which emoji (if any) would be used to convey distinct intentions when sending a message to a stranger (Study 2). Results from Study 1 showed that participants perceived messages with (or without emoji) to signal friendship intentions, with (or ) to signal romantic intentions, and with (or ) to signal sexual intentions. Results were consistent across social platforms. Study 2 replicated the results regarding the impact of emoji use on perceived intentions. When asked to take the sender's perspective, participants selected for friendship intentions, or for romantic intentions, and for sexual intentions. Still, about one-third of participants chose not to include emoji in initial interactions. Taken together, these findings suggest that emoji play an important role in online interpersonal communications and potentially shape the initiation of new relationships.